A REVOLUTION IN HEALTH MONITORING - Loso Judijanto; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
The revolution in health monitoring is characterised by the utilisation of digital technologies, including mobile apps and wearable devices, which enable real-time health monitoring. These technologies help individuals track various health indicators such as physical activity, nutritional intake, and sleep quality, and provide medical professionals with valuable data for more precise diagnosis and treatment. In addition, telemedicine expands healthcare access through remote consultations and improves adherence to treatment plans with reminders and early alerts. Overall, these innovations give individuals more control over their own health and strengthen interactions with healthcare providers.